Redistribution of powers and finances between Samara local self-government bodies during the intracity division reform in 2015–2020 - M. N. Matveev (Вестник Самарского университета: История, педагогика, филология, 2022)
In 2015, a local self-government reform in the form of the creation of intracity districts has been implemented in Samara. Formally, each intracity district became an independent municipality, with its own representative body, the Council of Deputies, the head of administration elected by it, and its own budget. This required a redistribution of powers between the city level of government and intracity areas. At the start of the reform, it was declared that its main goal was bringing the government closer to the people. Therefore, it was expected that many important powers would be transferred to the district level. It was also expected that financial resources would be transferred along with these powers. Only in this case, the newly created municipalities at the level of Samara's urban districts could become full-fledged authorities. And the population of the districts would be able to receive most municipal services directly where they live. Also, deputies of numerous district councils would be able to perform their duties more efficiently. However, in practice it turned out that city officials are unwilling to share power and financial resources. And many powers cannot work at the district level due to the fact that their implementation requires constant coordination with the mayor of the city. In 20192020, the Local Self-Government Committee of the Samara Provincial Duma, under the leadership of the author, analyzed the results of the reform, which provided a lot of factual material. One of the areas of analysis was the redistribution of powers, which showed that most of the powers previously transferred to the district level were then taken back as well as finances, the self-government of the districts turned out to be a fiction. The results of the analysis of powers are presented in this publication. It should be said that the inefficiency of the model of local self-government with intra-city division obviously does not stem from its nature, but is directly related to the situation when the city level of government, together with the governor's, actually discredit it in the eyes of the population, depriving it of real powers and financial resources.